Bark extract of the Amazonian tree Endopleura uchi (Humiriaceae) extends lifespan and enhances stress resistance in Caenorhabditis elegans - Peixoto, Herbenya; Roxo, Mariana; Silva, Emerson; Valente, Karla; Braun, Markus S.; Wang, Xiaojuan; Wink, Michael (Molecules, 2019)
Endopleura uchi (Huber) Cuatrec (Humiriaceae), known as uxi or uxi-amarelo in Brazil, is an endemic tree of the Amazon forest. In traditional medicine, its stem bark is used to treat a variety of health disorders, including cancer, diabetes, arthritis, uterine inflammation, and gynecological infections. According to HPLC analysis, the main constituent of the bark extract is the polyphenol bergenin. In the current study, we demonstrate by in vitro and in vivo experiments the antioxidant potential of a water extract from the stem bark of E. uchi. When tested in the model organism Caenorhabditis elegans, the extract enhanced stress resistance via the DAF-16/FOXO pathway. Additionally, the extract promoted an increase in the lifespan of the worms independent from caloric restriction. It also attenuated the age-related muscle function decline and formation of polyQ40 plaques, as a model for Huntington’s disease. Thus, these data support anti-aging and anti-oxidant properties of E. uchi, which has not yet been described. More studies are needed to assess the real benefits of E. uchi bark for human health and its toxicological profile.
Gesehen am 11.07.2019